2017
DOI: 10.1128/jb.00847-16
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic Regulation of Virulence Genes in Streptococcus mutans by the Conserved Small Protein SprV

Abstract: Streptococcus mutans, an oral pathogen associated with dental caries, colonizes tooth surfaces as polymicrobial biofilms known as dental plaque. S. mutans expresses several virulence factors that allow the organism to tolerate environmental fluctuations and compete with other microorganisms. We recently identified a small hypothetical protein (90 amino acids) essential for the normal growth of the bacterium. Inactivation of the gene, SMU.2137, encoding this protein caused a significant growth defect and loss o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The sensitivity of various S. mutans strains to different stressors was measured as described previously, with some modifications ( 52 54 ). Briefly, cells were grown from a 1:20 dilution in BHI overnight at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…The sensitivity of various S. mutans strains to different stressors was measured as described previously, with some modifications ( 52 54 ). Briefly, cells were grown from a 1:20 dilution in BHI overnight at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…The osmotic stress assay was performed as previously described (Shankar et al., 2017). Briefly, an overnight culture grown in BHI medium was diluted (1:100) in the same medium and incubated aerobically at 37°C to OD 600 = 0.1.…”
Section: Methodsmentioning
confidence: 99%
“…The streptococcal pleiotropic regulator of virulence (SprV) is a small hypothetical protein that is encoded by smu.2137 in S. mutans . The deletion of SprV leads to an impaired biofilm formation and various virulence-related functions in S. mutans [ 106 ]. Transcriptome sequencing revealed that gtfB, gbpA, gbpB , and gbpC , which are genes related to biofilm formation, are downregulated by 2.6-, 2.4-, 1.7-, and 2.6-fold, respectively [ 106 ].…”
Section: Regulation Of S Mutans Biofilm Formation ...mentioning
confidence: 99%
“… [ 105 ] sprV Smu.2137 Deletion of sprV inhibited exopolysaccharides synthesis and biofilm formation in S. mutans. [ 106 ] recA Smu.2085 Deletion of recA in S. mutans produced lower density biofilm. [ 107 ] …”
Section: Regulation Of S Mutans Biofilm Formation ...mentioning
confidence: 99%